A Source-Critical Translation of the Apocryphon of John (Short Recension) - Thomassen, Einar (Gnosis, 2025)
The revelation dialogue entitled The Apocryphon of John was built around an older text which had the form of a treatise. That treatise in turn made use of several sources, one of which was a version of the same treatise that Irenaeus reports in Haer. 1.29. This article offers a reconstruction of the short recension of Ap. John in its original form based on a comparison of the manuscript witnesses and visualises typographically the various layers of the text.